Clinker-free low-carbon cementing material and preparation method thereof
A clinker-free low-carbon cementitious material using activated diatomite and bauxite with nano-enhancers addresses high energy consumption and emissions in traditional cement production, improving mechanical properties and durability for construction applications.
Patent Information
- Application Number
- CN202411341626.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2024-12-27
AI Technical Summary
The traditional cement industry faces high energy consumption and carbon emissions due to the production of ordinary Portland cement, which requires high-temperature calcination, and there is a need to improve the utilization of low-grade diatomaceous earth and bauxite waste while reducing cement production costs.
A clinker-free low-carbon cementitious material is prepared using activated diatomite and bauxite as active components, combined with liquid sodium silicate and sodium hydroxide as activators, and nano-enhancers like nano-silicon dioxide and nano-alumina to enhance strength and durability, while avoiding high-temperature calcination.
This approach significantly reduces carbon dioxide emissions, improves mechanical properties and durability, and enhances the adaptability of the material to meet various engineering requirements, making it suitable for modern construction applications.
Smart Images

Figure CN119191773A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and in particular relates to a clinker-free low-carbon cementitious material and a preparation method thereof. Background Art
[0002] With global attention to climate change, the traditional cement industry is facing tremendous pressure due to its high energy consumption and high carbon emissions. Ordinary Portland cement produces a large amount of carbon dioxide during the production process, mainly from the preparation of clinker by calcining limestone. Therefore, the development of alternative cementitious materials with low or even no carbon emissions has become a key research direction in the fields of materials science and construction engineering. In recent years, clinker-free cementitious materials have attracted much attention due to their green and environmentally friendly characteristics. This type of material does not require high-temperature calcination, achieves cementitious properties through a chemical excitation mechanism, and significantly reduces carbon emissions. Its common raw materials include industrial by-products and natural resources, such as silicate waste, slag, fly ash and diatomaceous earth. This not only reduces the carbon footprint, but also realizes the effective utilization of industrial waste and improves the sustainability of materials.
[0003] In the research and development of clinker-free low-carbon cementitious materials, the application of diatomite and bauxite waste residue has gradually attracted the attention of researchers. Diatomite is a natural silicate mineral, mainly composed of fine diatom remains, with high porosity and large specific surface area. As an industrial by-product, diatomite waste residue has been widely used in filtration, adsorption and catalysis, but its application research in cementitious materials is still in its infancy.
[0004] On the other hand, bauxite slag is a by-product of the aluminum industry. Its main components are alumina and silicon dioxide, which have high chemical activity and strong high temperature resistance. At present, bauxite slag has been used in refractory materials, building materials and other fields, but its application in clinker-free cementitious materials is still in the exploratory stage. Summary of the invention
[0005] The purpose of the present invention is to solve the problems of high energy consumption and high carbon emission of traditional cement-based materials, improve the utilization rate of low-grade diatomaceous earth and bauxite waste and reduce the cost of cement production, and provide a clinker-free low-carbon cementitious material and a preparation method thereof.
[0006] A clinker-free low-carbon cementitious material is prepared from 600 parts of active components, 281 to 382 parts of activator components, 6 to 30 parts of nano-enhancers, 3 to 20 parts of calcium supplements and 2 to 10 parts of organic solvents by weight.
[0007] The 600 parts of active components are composed of 210 to 300 parts of activated diatomaceous earth and 300 to 390 parts of bauxite;
[0008] The 281-382 parts of activator components are composed of 46-176 parts of liquid sodium silicate, 13-39 parts of sodium hydroxide, 175-290 parts of water and 10-20 parts of water reducing agent.
[0009] A method for preparing a clinker-free low-carbon cementitious material is specifically completed by the following steps:
[0010] 1. Preparation of activated diatomite:
[0011] The diatomaceous earth is calcined at 600°C to 650°C for 2h to 3h, and then rapidly cooled to obtain activated diatomaceous earth; the activated diatomaceous earth is mechanically ground to obtain activated diatomaceous earth powder;
[0012] 2. Preparation of alkaline activator:
[0013] ①. Weigh 46 to 176 parts of liquid sodium silicate, 13 to 39 parts of sodium hydroxide, 175 to 290 parts of water and 10 to 20 parts of water reducer by mass;
[0014] ②, mix 46 to 176 parts of liquid sodium silicate weighed in step 2① with 13 to 39 parts of sodium hydroxide, stir evenly, then add 175 to 290 parts of water and 10 to 20 parts of water reducer, stir evenly, and then seal and stand for 20 to 24 hours to obtain an alkali activator;
[0015] 3. Powder mixing:
[0016] ①, weigh 600 parts of active components, 281 to 382 parts of stimulator components, 6 to 30 parts of nano-enhancers, 3 to 20 parts of calcium supplements and 2 to 10 parts of organic solvents according to mass proportions;
[0017] ②, add 600 parts of active components, 6 parts to 30 parts of nano-enhancers, 3 parts to 20 parts of calcium supplements and 2 parts to 10 parts of organic solvents weighed into a stirring device, and stir to mix the powders evenly to obtain mixed powder I;
[0018] Fourth, the mixed powder I is mixed with half of the activator component, stirred, and then the remaining activator component is added, and stirred to obtain a mixed slurry II;
[0019] 5. Add the mixed slurry II into the mold, vibrate and shape it, and then obtain the clinker-free low-carbon cementitious material after curing.
[0020] The advantages and positive effects of the present invention are:
[0021] (1) The clinker-free low-carbon cementitious material of the present invention uses activated diatomite and bauxite as the main active components to replace traditional cement clinker, thereby greatly reducing carbon dioxide emissions during cement production. This low-carbon system not only meets the current environmental protection requirements of the building materials industry, but also provides an effective technical means for achieving the goal of carbon neutrality. Compared with traditional cement production, the present invention avoids the high-temperature calcination of clinker, fundamentally reducing energy consumption and carbon footprint.
[0022] (2) The activator components used in the clinker-free low-carbon cementitious material of the present invention include liquid sodium silicate and sodium hydroxide, which can effectively improve the early strength and durability of the material; in addition, the addition of nano-enhancers such as nano-silicon dioxide and nano-alumina further densifies the microstructure of the material, thereby enhancing the overall strength and crack resistance of the material; such a modification effect not only significantly improves the mechanical properties of the material, but also improves its durability and chemical corrosion resistance, and is suitable for application in various complex environments;
[0023] (3) The clinker-free low-carbon cementitious material of the present invention also has strong adaptability; by reasonably adjusting the ratio of the activator, nano-enhancer and calcium supplement, the performance of the material can be adjusted to meet different engineering requirements; for example, the use of water reducers and organic solvents such as styrene-acrylic emulsion in the mix not only effectively reduces the water consumption of the material, but also improves its fluidity, making the material's operating performance during the construction process more excellent. This is of great significance for improving the efficiency of modern construction;
[0024] (4) The present invention provides an effective technical means for achieving the goal of carbon neutrality. At the same time, compared with traditional cement production, it avoids the high-temperature calcination of clinker, fundamentally reducing energy consumption and carbon footprint. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a scanning electron microscope image of unactivated diatomite;
[0026] Figure 2 This is a scanning electron microscope image of activated diatomite;
[0027] Figure 3 is the XRD pattern of activated diatomite;
[0028] Figure 4 is the XRD diffraction pattern of bauxite;
[0029] Figure 5 is the particle size distribution diagram of activated diatomite;
[0030] Figure 6 This is the particle size distribution diagram of bauxite. DETAILED DESCRIPTION
[0031] Specific implementation method 1: This implementation method is a clinker-free low-carbon cementitious material, which is prepared by 600 parts of active components, 281 to 382 parts of activator components, 6 to 30 parts of nano-enhancers, 3 to 20 parts of calcium supplements and 2 to 10 parts of organic solvents in parts by mass;
[0032] The 600 parts of active components are composed of 210 to 300 parts of activated diatomaceous earth and 300 to 390 parts of bauxite;
[0033] The 281-382 parts of activator components are composed of 46-176 parts of liquid sodium silicate, 13-39 parts of sodium hydroxide, 175-290 parts of water and 10-20 parts of water reducing agent.
[0034] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that the main components of the activated diatomaceous earth are: 92.1% SiO2, 3.12% Al2O3, and the ignition loss is 2.72%. The other steps are the same as those of specific implementation method 1.
[0035] Specific implementation method 3: This implementation method is different from specific implementation method 1 or 2 in that the main components of the bauxite are: 33.62% SiO2, 61.57% Al2O3, and the ignition loss is 1.55%. The other steps are the same as those of specific implementation method 1 or 2.
[0036] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that the modulus of the liquid sodium silicate is 2.3, the Na2O content is not less than 13.75%, and the SiO2 content is not less than 29.99%. The other steps are the same as those of specific embodiments 1 to 3.
[0037] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that: the 6 to 30 parts of the nano-enhancer are composed of 2 to 8 parts of nano-silicon dioxide, 2 to 10 parts of nano-alumina and 2 to 20 parts of nano-calcium carbonate; the average particle size of the nano-silicon dioxide is not greater than 50nm; the average particle size of the nano-alumina is not greater than 30nm; the average particle size of the nano-calcium carbonate is not greater than 50nm. The other steps are the same as those of specific embodiments 1 to 4.
[0038] Specific embodiment 6: This embodiment differs from specific embodiments 1 to 5 in that: the 3 to 20 parts of calcium supplements are composed of 1 to 15 parts of calcium chloride, 1 to 18 parts of calcium sulfate and 1 to 20 parts of calcium oxide; the content of calcium chloride is not less than 96%; the content of calcium sulfate is not less than 97%, and the content of calcium oxide is not less than 98%. The other steps are the same as those of specific embodiments 1 to 5.
[0039] Specific embodiment 7: This embodiment differs from specific embodiments 1 to 6 in that: the organic solvent is styrene acrylic emulsion, which is obtained by emulsion copolymerization of styrene and acrylate monomers; the water reducer is a naphthalene-based high-efficiency water reducer, model FDN-C, purchased from Shandong Wanshan Chemical Co., Ltd. The other steps are the same as specific embodiments 1 to 6.
[0040] Specific embodiment 8: This embodiment differs from specific embodiments 1 to 7 in that the method for preparing the clinker-free low-carbon cementitious material is specifically completed according to the following steps:
[0041] 1. Preparation of activated diatomite:
[0042] The diatomaceous earth is calcined at 600°C to 650°C for 2h to 3h, and then rapidly cooled to obtain activated diatomaceous earth; the activated diatomaceous earth is mechanically ground to obtain activated diatomaceous earth powder;
[0043] 2. Preparation of alkaline activator:
[0044] ①. Weigh 46 to 176 parts of liquid sodium silicate, 13 to 39 parts of sodium hydroxide, 175 to 290 parts of water and 10 to 20 parts of water reducer by mass;
[0045] ②, mix 46 to 176 parts of liquid sodium silicate weighed in step 2① with 13 to 39 parts of sodium hydroxide, stir evenly, then add 175 to 290 parts of water and 10 to 20 parts of water reducer, stir evenly, and then seal and stand for 20 to 24 hours to obtain an alkali activator;
[0046] 3. Powder mixing:
[0047] ①, weigh 600 parts of active components, 281 to 382 parts of stimulator components, 6 to 30 parts of nano-enhancers, 3 to 20 parts of calcium supplements and 2 to 10 parts of organic solvents according to mass proportions;
[0048] ②, add 600 parts of active components, 6 parts to 30 parts of nano-enhancers, 3 parts to 20 parts of calcium supplements and 2 parts to 10 parts of organic solvents weighed into a stirring device, and stir to mix the powders evenly to obtain mixed powder I;
[0049] Fourth, the mixed powder I is mixed with half of the activator component, stirred, and then the remaining activator component is added, and stirred to obtain a mixed slurry II;
[0050] 5. Add the mixed slurry II into the mold, vibrate and shape it, and then obtain the clinker-free low-carbon cementitious material after curing. The other steps are the same as those of the specific embodiments 1 to 7.
[0051] Specific embodiment 9: The difference between this embodiment and specific embodiments 1 to 8 is that the quenching described in step 1 is: placing the calcined diatomaceous earth at 20±2°C for quenching; the particle size of the diatomaceous earth powder described in step 1 is mainly distributed in the range of 10μm to 45μm, and the specific surface area is 320m 2 / kg~380m 2 / kg. The other steps are the same as those in the first to eighth embodiments.
[0052] Specific embodiment 10: The difference between this embodiment and specific embodiments 1 to 9 is that: the stirring speed described in step 3② is 100r / min~150r / min, and the stirring time is 8min~10min; the stirring speed described in step 4 is 100r / min~300r / min, and the total stirring time is 5min~8min; the vibration molding time described in step 5 is 50s~60s; the curing conditions described in step 5 are: first steam curing at 55℃~65℃ for 20h~30h, and then curing at a temperature of 20±2℃ and a relative humidity of ≥95% for up to 28 days. The other steps are the same as specific embodiments 1 to 9.
[0053] The following examples are used to verify the beneficial effects of the present invention:
[0054] Embodiment 1: A method for preparing a clinker-free low-carbon cementitious material is specifically completed by the following steps:
[0055] 1. Preparation of activated diatomite:
[0056] The original diatomite is calcined at 600°C for 2 hours, and then cooled at room temperature (20±2°C) to obtain activated diatomite; the activated diatomite is ground at a grinding speed of 1000 r / min and a grinding time of 6 minutes to obtain activated diatomite powder;
[0057] 2. Preparation of alkaline activator:
[0058] ①, weigh 93 parts of liquid sodium silicate, 30 parts of sodium hydroxide, 218 parts of water and 10 parts of water reducer by mass; the water reducer is a naphthalene-based high-efficiency water reducer, model FDN-C, purchased from Shandong Wanshan Chemical Co., Ltd.;
[0059] ②, mix 93 parts of liquid sodium silicate weighed in step 2① with 30 parts of sodium hydroxide, stir evenly, then add 218 parts of water and 10 parts of water reducer, stir evenly, and let stand for 24 hours to obtain an alkali activator;
[0060] 3. Powder mixing:
[0061] ①. Weigh 600 parts of active components, 359 parts of stimulator components, 6 parts of nano-enhancers, 3 parts of calcium supplements and 2 parts of organic solvents by mass;
[0062] The 600 parts of active components described in step 3① are composed of 210 parts of activated diatomaceous earth and 390 parts of bauxite;
[0063] The 6 parts of nano-enhancers described in step 3① are composed of 2 parts of nano-silicon dioxide, 2 parts of nano-aluminum oxide and 2 parts of nano-calcium carbonate;
[0064] The three parts of calcium supplements described in step 3① are composed of 1 part of calcium chloride, 1 part of calcium sulfate and 1 part of calcium oxide; the content of the calcium chloride is not less than 96%; the content of the calcium sulfate is not less than 97%, and the content of the calcium oxide is not less than 98%;
[0065] The organic solvent described in step 3① is styrene acrylic emulsion, which is obtained by emulsion copolymerization of styrene and acrylate monomers;
[0066] ②, add 600 parts of active components, 6 parts of nano-enhancers, 3 parts of calcium supplements and 2 parts of organic solvents into a stirring device, stir to mix the powders evenly, and obtain mixed powder I;
[0067] The stirring speed in step 3② is 150r / min and the stirring time is 10min;
[0068] Fourth, mix the mixed powder I with half of the activator component, stir at 150r / min for 2min; then add the remaining activator component, stir at 250r / min for another 5min to obtain mixed slurry II;
[0069] 5. Add the mixed slurry II into the mold, then vibrate it into shape, steam it at 60°C for 24 hours, and then cure it at a temperature of 20±2°C and a relative humidity of ≥95% for 28 days to obtain a clinker-free low-carbon cementitious material.
[0070] The properties of the clinker-free low-carbon cementitious material prepared in Example 1 were measured, and specific results were obtained: the 7d compressive strength was 24.7MPa, and the 28d compressive strength was 23.4MPa.
[0071] Example 2: The difference between this example and Example 1 is that: Step 2① weighs 116 parts of liquid sodium silicate, 26 parts of sodium hydroxide, 175 parts of water and 18 parts of water reducer by mass; the 600 parts of active components described in Step 3① are composed of 240 parts of activated diatomaceous earth and 360 parts of bauxite. The other steps and parameters are the same as those in Example 1.
[0072] The properties of the clinker-free low-carbon cementitious material prepared in Example 2 were measured, and specific results were obtained: the 7d compressive strength was 26.3MPa, and the 28d compressive strength was 23.4MPa.
[0073] Example 3: The difference between this example and Example 1 is that: Step 2① weighs 135 parts of liquid sodium silicate, 30 parts of sodium hydroxide, 194 parts of water and 18 parts of water reducer by mass; the 600 parts of active components described in Step 3① consist of 270 parts of activated diatomaceous earth and 330 parts of bauxite. The other steps and parameters are the same as those in Example 1.
[0074] The properties of the clinker-free low-carbon cementitious material prepared in Example 3 were measured, and specific results were obtained: the 7d compressive strength was 25.9 MPa, and the 28d compressive strength was 23.5 MPa.
[0075] Example 4: The difference between this comparative example and Example 1 is that: in step 2①, 93 parts of liquid sodium silicate, 30 parts of sodium hydroxide, 180 parts of water, and 18 parts of water reducer are weighed by mass; in step 3①, 600 parts of active components, 359 parts of activator components, 8 parts of nano-enhancers, 3 parts of calcium supplements, and 2 parts of organic solvents are weighed by mass; the 8 parts of nano-enhancers are composed of 4 parts of nano-silicon dioxide, 2 parts of nano-alumina, and 2 parts of nano-calcium carbonate. The other steps and parameters are the same as those in Example 1.
[0076] The properties of the cementitious material prepared in Example 4 were measured, and specific results were obtained: the 7d compressive strength was 27.8 MPa, and the 28d compressive strength was 27.2 MPa.
[0077] Example 5: The difference between this comparative example and Example 1 is that: in step 2①, 93 parts of liquid sodium silicate, 30 parts of sodium hydroxide, 175 parts of water, and 18 parts of water reducer are weighed by mass; in step 3①, 600 parts of active components, 359 parts of activator components, 8 parts of nano-enhancers, 3 parts of calcium supplements, and 2 parts of organic solvents are weighed by mass; the 8 parts of nano-enhancers are composed of 2 parts of nano-silicon dioxide, 4 parts of nano-alumina, and 2 parts of nano-calcium carbonate. The nano-enhancer is nano-alumina. The other steps and parameters are the same as those in Example 1.
[0078] The properties of the cementitious material prepared in Example 5 were measured, and specific results were obtained: the 7d compressive strength was 26.7 MPa, and the 28d compressive strength was 26.6 MPa.
[0079] Example 6: The difference between this comparative example and Example 2 is that: in step 2①, 93 parts of liquid sodium silicate, 30 parts of sodium hydroxide, 180 parts of water, and 18 parts of water reducer are weighed by mass; in step 3①, 600 parts of active components, 359 parts of activator components, 18 parts of nano-enhancers, 3 parts of calcium supplements, and 2 parts of organic solvents are weighed by mass; the 18 parts of nano-enhancers are composed of 2 parts of nano-silicon dioxide, 2 parts of nano-alumina, and 14 parts of nano-calcium carbonate. The other steps and parameters are the same as those in Example 2.
[0080] The properties of the cementitious material prepared in Example 6 were measured, and specific results were obtained: the 7d compressive strength was 28.8 MPa, and the 28d compressive strength was 29.1 MPa.
[0081] Example 7: The difference between this comparative example and Example 2 is that: in step 2①, 93 parts of liquid sodium silicate, 30 parts of sodium hydroxide, 180 parts of water, and 18 parts of water reducer are weighed by mass; in step 3①, 600 parts of active components, 359 parts of activator components, 6 parts of nano-enhancers, 12 parts of calcium supplements, and 2 parts of organic solvents are weighed by mass; the 12 parts of calcium supplements are composed of 8 parts of calcium chloride, 2 parts of calcium sulfate, and 2 parts of calcium oxide. The other steps and parameters are the same as those in Example 2.
[0082] The properties of the cementitious material prepared in Example 7 were measured, and specific results were obtained: the 7d compressive strength was 28.9 MPa, and the 28d compressive strength was 27.6 MPa.
[0083] Example 8: The difference between this comparative example and Example 3 is that: in step 2①, 93 parts of liquid sodium silicate, 30 parts of sodium hydroxide, 185 parts of water, and 18 parts of water reducer are weighed by mass; in step 3①, 600 parts of active components, 359 parts of activator components, 6 parts of nano-enhancers, 12 parts of calcium supplements, and 2 parts of organic solvents are weighed by mass; the 12 parts of calcium supplements are composed of 2 parts of calcium chloride, 2 parts of calcium sulfate, and 8 parts of calcium oxide. The other steps and parameters are the same as those in Example 3.
[0084] The properties of the cementitious material prepared in Example 8 were measured, and specific results were obtained: the 7d compressive strength was 29.6 MPa, and the 28d compressive strength was 28.7 MPa.
[0085] Example 9: The difference between this comparative example and Example 3 is that: in step 2①, 93 parts of liquid sodium silicate, 30 parts of sodium hydroxide, 185 parts of water, and 18 parts of water reducer are weighed by mass; in step 3①, 600 parts of active components, 359 parts of activator components, 6 parts of nano-enhancers, 12 parts of calcium supplements, and 2 parts of organic solvents are weighed by mass; the 12 parts of calcium supplements are composed of 2 parts of calcium chloride, 8 parts of calcium sulfate, and 2 parts of calcium oxide. The other steps and parameters are the same as those in Example 3.
[0086] The properties of the cementitious material prepared in Example 9 were measured, and specific results were obtained: the 7d compressive strength was 25.3 MPa, and the 28d compressive strength was 23.6 MPa.
[0087] Example 10: The difference between this comparative example and Example 4 is that in step 2①, 93 parts of liquid sodium silicate, 30 parts of sodium hydroxide, 190 parts of water, and 10 parts of water reducer are weighed by mass; in step 3①, 600 parts of active components, 359 parts of activator components, 6 parts of nano-enhancers, 3 parts of calcium supplements, and 6 parts of organic solvents are weighed by mass; the organic solvent is styrene-acrylic emulsion. The other steps and parameters are the same as those in Example 4.
[0088] The properties of the cementitious material prepared in Example 10 were measured, and specific results were obtained: the 7d compressive strength was 28.9 MPa, and the 28d compressive strength was 29.3 MPa.
[0089] Figure 1 This is a scanning electron microscope image of unactivated diatomite;
[0090] Figure 2 This is a scanning electron microscope image of activated diatomite;
[0091] from Figure 1 and Figure 2 It can be seen that compared with the original diatomite, after heat treatment at 600°C, there are basically no impurities on the surface and body of the round sieve-shaped diatomite, and micropores appear around and in the middle of the diatomite. The pore size becomes more uniform and has good permeability.
[0092] Figure 3 is the XRD pattern of activated diatomite;
[0093] Figure 4 is the XRD diffraction pattern of bauxite;
[0094] like Figure 3 , 4As shown, the 600℃ activated diatomite and bauxite raw materials used were analyzed by XRD. It can be seen that the 600℃ activated diatomite and bauxite mainly contain silica phase and alumina phase. This phase gives the 600℃ activated diatomite and bauxite certain potential activity, providing a material basis for the formation of CSH gel in the reaction product.
[0095] Figure 5 is the particle size distribution diagram of activated diatomite;
[0096] Figure 6 This is the particle size distribution diagram of bauxite.
[0097] like Figures 5-6 As shown, the 600°C activated diatomaceous earth and bauxite raw materials used in the embodiment are analyzed by laser particle size analysis. It can be seen that the content of activated diatomaceous earth with a particle size of less than 45 μm is not less than 99%, and the content of bauxite with a particle size of less than 45 μm is not less than 95%.
[0098] Analysis of the performance test results of the clinker-free low-carbon cementitious material shows that in the diatomite-bauxite binary low-carbon cementitious material system, the amorphous silica and alumina of calcined diatomite and bauxite play a good chemical reaction under the alkali activation system. Compared with the strength of the published diatomite-based cementitious materials (about 10MPa), this patent significantly improves the mechanical strength of diatomite and cementitious materials. In short, the cementitious material prepared by the present invention has good net slurry strength, can be used instead of cement, and is more environmentally friendly.
[0099] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A clinker-free low-carbon cementitious material, characterized in that The clinker-free low-carbon cementitious material is prepared from 600 parts of active components, 281 to 382 parts of activator components, 6 to 30 parts of nano-enhancers, 3 to 20 parts of calcium supplements and 2 to 10 parts of organic solvents in parts by mass; The 600 parts of active components are composed of 210 to 300 parts of activated diatomaceous earth and 300 to 390 parts of bauxite; The 281-382 parts of activator components are composed of 46-176 parts of liquid sodium silicate, 13-39 parts of sodium hydroxide, 175-290 parts of water and 10-20 parts of water reducing agent.
2. The clinker-free low-carbon cementitious material according to claim 1, characterized in that The main components of the activated diatomaceous earth are: 92.1% SiO2, 3.12% Al2O3, and the ignition loss is 2.72%.
3. The clinker-free low-carbon cementitious material according to claim 1, characterized in that The main components of the bauxite are: 33.62% SiO2, 61.57% Al2O3, and the ignition loss is 1.55%.
4. The clinker-free low-carbon cementitious material according to claim 1, characterized in that The modulus of the liquid sodium silicate is 2.3, the Na2O content is not less than 13.75%, and the SiO2 content is not less than 29.99%.
5. The clinker-free low-carbon cementitious material according to claim 1, characterized in that The 6 to 30 parts of nano-enhancer are composed of 2 to 8 parts of nano-silicon dioxide, 2 to 10 parts of nano-aluminum oxide and 2 to 20 parts of nano-calcium carbonate; the average particle size of the nano-silicon dioxide is not greater than 50nm; the average particle size of the nano-aluminum oxide is not greater than 30nm; the average particle size of the nano-calcium carbonate is not greater than 50nm.
6. The clinker-free low-carbon cementitious material according to claim 1, characterized in that The 3 to 20 parts of calcium supplement are composed of 1 to 15 parts of calcium chloride, 1 to 18 parts of calcium sulfate and 1 to 20 parts of calcium oxide; the content of the calcium chloride is not less than 96%; the content of the calcium sulfate is not less than 97%; and the content of the calcium oxide is not less than 98%.
7. The clinker-free low-carbon cementitious material according to claim 1, characterized in that The organic solvent is styrene acrylic emulsion, which is obtained by emulsion copolymerization of styrene and acrylate monomers; the water reducer is a naphthalene-based high-efficiency water reducer, model FDN-C.
8. The method for preparing a clinker-free low-carbon cementitious material according to claim 1, characterized in that The method for preparing the clinker-free low-carbon cementitious material is specifically completed according to the following steps:
1. Preparation of activated diatomaceous earth: The diatomaceous earth is calcined at 600°C to 650°C for 2h to 3h, and then rapidly cooled to obtain activated diatomaceous earth; the activated diatomaceous earth is mechanically ground to obtain activated diatomaceous earth powder; 2. Preparation of alkaline activator: ①. Weigh 46 to 176 parts of liquid sodium silicate, 13 to 39 parts of sodium hydroxide, 175 to 290 parts of water and 10 to 20 parts of water reducer by mass; ②, mix 46 to 176 parts of liquid sodium silicate weighed in step 2① with 13 to 39 parts of sodium hydroxide, stir evenly, then add 175 to 290 parts of water and 10 to 20 parts of water reducer, stir evenly, and then seal and stand for 20 to 24 hours to obtain an alkali activator; 3. Powder mixing: ①, weigh 600 parts of active components, 281 to 382 parts of stimulator components, 6 to 30 parts of nano-enhancers, 3 to 20 parts of calcium supplements and 2 to 10 parts of organic solvents by mass; ②, add 600 parts of active components, 6 parts to 30 parts of nano-enhancers, 3 parts to 20 parts of calcium supplements and 2 parts to 10 parts of organic solvents weighed into a stirring device, and stir to mix the powders evenly to obtain mixed powder I; Fourth, the mixed powder I is mixed with half of the activator component, stirred, and then the remaining activator component is added, and stirred to obtain a mixed slurry II; 5. Add the mixed slurry II into the mold, vibrate and shape it, and then obtain the clinker-free low-carbon cementitious material after curing.
9. The method for preparing a clinker-free low-carbon cementitious material according to claim 8, characterized in that The rapid cooling in step 1 is as follows: placing the calcined diatomite at 20±2°C for rapid cooling; the particle size of the diatomite powder in step 1 is mainly distributed in the range of 10μm to 45μm, and the specific surface area is 320m 2 / kg~380m 2 / kg.
10. The method for preparing a clinker-free low-carbon cementitious material according to claim 8, characterized in that The stirring speed described in step 3② is 100r / min~150r / min, and the stirring time is 8min~10min; the stirring speed described in step 4 is 100r / min~300r / min, and the total stirring time is 5min~8min; the vibration molding time described in step 5 is 50s~60s; the curing conditions described in step 5 are: first steam-cured at 55℃~65℃ for 20h~30h, and then cured at a temperature of 20±2℃ and a relative humidity of ≥95% for up to 28 days.
Citation Information
Patent Citations
Preparation method of alkali-activated high-silica bauxite ore based gel material with adjustable electric conductivity
CN105731895A
Green alkali-activated material for repair and protection and preparation method thereof
CN112521115A
Alkali-activated cementing material with low drying shrinkage and high compressive strength and preparation method thereof
CN115432989A
Method for preparing cement admixture from diatomite and bauxite and application of cement admixture
CN118598559A
Cited By
Cementing material based on large-dosage shield muck as well as preparation method and application of cementing material
CN121517148A
A cementitious material based on large amount of shield muck and a preparation method and application thereof
CN121517148B
